ISLAMIC BOARDING SCHOOL-BASED MADRASAH CONFLICT MANAGEMENT - Hasanah, Maulidatul; Aisyah, Nur; Abdullah, Abdullah; Abdurrahman, Abdurrahman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study explores and analyzes the conflict management of pesantren-based madrasahs, especially madrasahs, in the educational environment. The conflict has both positive and negative impacts, such as the conflict in the madrasah environment, which includes a decrease in the mutual of teachers and groups in the world of education, which hinders effective communication. This research focuses on finding pesantren-based conflict management in MA Nurul Jadid, which aims to understand conflict dynamics, analyze conflict sources, impact on the learning environment, evaluate the effectiveness of conflict management strategies, and develop a contextualized model. The research method includes identifying patterns, themes, and nuances from interviews and observations. This study describes how pesantren values are implemented in daily life in madrasah, especially in the context of conflict management. The results showed that pesantren values became an essential foundation in their approach to conflict, creating an environment filled with brotherhood and deliberation. Training and discussion forums support creating a school culture that reflects these values. This research is expected to contribute value to understanding conflict management in pesantren, particularly in MA Nurul Jadid, and enrich the literature related to conflict management in pesantren-based educational institutions.